Frustration in the Pattern Formation of Polysyllabic Words - Hayata, Kazuya (Frontiers in Physics, 2017)
A novel frustrated system is given for the analysis of (m + 1)-syllabled vocal sounds for languages with the m-vowel system, where the varieties of vowels are assumed to be m (m > 2). The necessary and sufficient condition for observing the sound frustration is that the configuration of m vowels in an m-syllabled word has a preference for the ‘repulsive’ type, in which there is no duplication of an identical vowel. For languages that meet this requirement, no (m + 1)-syllabled word can in principle select the present type because at most m different vowels are available and consequently the duplicated use of an identical vowel is inevitable. For languages showing a preference for the ‘attractive’ type, where an identical vowel aggregates in a word, there arises no such conflict. In this paper, we first elucidate for Arabic with m = 3 how to deal with the conflicting situation, where a statistical approach based on the chi-square testing is employed. In addition to the conventional three-vowel system, analyses are made also for Russian, where a polysyllabic word contains both a stressed and an indeterminate vowel. Through the statistical analyses the selection scheme for quadrisyllabic configurations is found to be strongly dependent on the parts of speech as well as the gender of nouns. In order to emphasize the relevance to the sound model of binary oppositions, analyzed results of Greek verbs are also given.